2005
DOI: 10.2320/matertrans.46.493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Oxide Dispersion Strengthened Steels Irradiated in JOYO

Abstract: Oxide dispersion strengthened (ODS) steels, which are candidate materials for water-cooled solid breeder blankets, were fabricated with several manufacturing parameters, and then irradiated in the experimental fast reactor JOYO to evaluate their irradiation behavior.Engineering stress strain curves of ODS steels irradiated at 673 K exhibited superior material response, i.e., increased tensile strength due to irradiation hardening and no loss of total elongation. Also, their temperature dependence of tensile pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The results of hardening at higher T irr are qualitatively consistent between the five different ODS alloys irradiated in JMTR to low doses (0.75 dpa) and three ODS alloys irradiated in HFIR over a range of doses (4.5-23.3 dpa). Irradiation hardening at 400 • C is also reported in JOYO reactor irradiated ∼12%Cr ODS steels between ∼2.5-21 dpa [162]. The unexpected hardening of ODS steels in figure 11 for T irr > 350 • C-400 • C is contrary to that in RAFM steels, where drastic recovery of radiation hardening occurs at higher temperatures and hardening almost completely subsides for T irr > 400 • C-450 • C with a tendency for some slight softening for T irr > ∼450 • C-500 • C (see figure 2).…”
Section: Lthe Comparison: Rafm Versus Ods Steelsmentioning
confidence: 56%
“…The results of hardening at higher T irr are qualitatively consistent between the five different ODS alloys irradiated in JMTR to low doses (0.75 dpa) and three ODS alloys irradiated in HFIR over a range of doses (4.5-23.3 dpa). Irradiation hardening at 400 • C is also reported in JOYO reactor irradiated ∼12%Cr ODS steels between ∼2.5-21 dpa [162]. The unexpected hardening of ODS steels in figure 11 for T irr > 350 • C-400 • C is contrary to that in RAFM steels, where drastic recovery of radiation hardening occurs at higher temperatures and hardening almost completely subsides for T irr > 400 • C-450 • C with a tendency for some slight softening for T irr > ∼450 • C-500 • C (see figure 2).…”
Section: Lthe Comparison: Rafm Versus Ods Steelsmentioning
confidence: 56%
“…However, the real mechanisms are still not clear and a combination of the three processes could be happening at the same time. Normally, the amount of added Y2O3 varies from in 0.25 to 0.35 % which is enough to promote a high dispersion of nanoparticles or even nanoclusters formations [96]. Nanocluster is the name given to nanooxides whose stoichiometry is not well defined.…”
Section: Oxide Dispersion Strengthened Steels: From F/m To Ferritic Omentioning
confidence: 99%
“…In the aspect of experiments, microstructure, orientation relationship with the matrix and performance of oxide particles were figured out [13][14][15]. S. Yamashita et al suggested that the oxide particles possessed significantly high stability under irradiation, and they would hinder dislocation movement and annihilate the radiation-induced defects in the matrix [8]. In the aspect of calculations, Fu et al proposed an O-vacancy mechanism that facilitates the nucleation and stabilization of O-riched particles [16].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of irradiation resistance is assumed to be correlated with the ultrafine oxide dispersion particles in the matrix, which would act as barriers against dislocation movement and effective sink sites for point defects [8]. The commonly used oxide particles in ODS steels are Y 2 O 3 , Y-Ti-O and/or Y-Al-O.…”
Section: Introductionmentioning
confidence: 99%